Spatially Resolved Crosslinking of Hydroxypropyl Cellulose Esters for the Generation of Functional Surface-Attached Organogels - Nau, Maximilian; Trosien, Simon; Seelinger, David; Boehm, Anna K.; Biesalski, Markus (Frontiers in Chemistry, 2019)
Chemistry, geometric shape and swelling behavior are the key parameters that determine any successful use of man-made polymeric networks (gels). While understanding of the swelling behavior of both water-swellable hydrogels and organogels that swell in organic solvents can be considered well-advanced with respect to fossil fuel-based polymer networks, the understanding, in particular, of wood-derived polymers in such a network architecture is still lacking. In this work, we focus on organogels derived from hydroxypropyl cellulose (HPC) ester. The latter polymer was functionalized with saturated and unsaturated fatty acids, respectively. Due to their tailored chemical constitution, we demonstrated that such polysaccharide can be crosslinked and simultaneously surface-bound by using a photo-induced radical reaction using a photo-initiator. Based on the choice of fatty acid used in the design of the HPC ester, and by controlling the degree of substitution (DS) obtained during the esterification of the polysaccharide, modular manipulation of the physical properties (e.g., polarity) of the resulting gel is possible. Depending on the initiator employed, different wavelengths of light, from UV to visible, can be utilized for the crosslinking reaction, which facilitates the deployment of a range of light sources and different lithographic methods. Additionally, we showed that altering of the illumination time allows to tailor the netpoint density, and thus, the degree of linear deformation in equilibrium and the swelling kinetics. Finally, we performed a proof-of-principle experiment to demonstrate the application of our material for the generation of spatially resolved polymer patches to enrich organic molecules from a solution within a microfluidic channel.